2000
DOI: 10.1002/jor.1100180606
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced proliferation and differentiation of human articular chondrocytes when seeded at low cell densities in alginate In Vitro

Abstract: Dedifferentiated human articular chondrocytes exhibited a wide variation in their capacity to proliferate and redifferentiate in an alginate suspension culture system. The greatest extent of proliferation and redifferentiation was seen to be dependent on the formation of clonal populations of chondrocytes and correlated inversely with the initial cell seeding density. Redifferentiating chondrocytes seeded at low density (1 x 10(4) cells/ml alginate) compared with chondrocytes that were seeded at high density (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
51
0
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 28 publications
6
51
0
1
Order By: Relevance
“…The differential expression of the cytokine CTGF by adult articular chondrocytes, within 48 hr of transfer to suspension culture at 10 6 cells/ml ( Fig. 2A) was consistent with relatively low level of cell proliferation observed in suspension culture (Gagne et al, 2000). CTGF expression had been previously identified in chondrocytes derived from growth plate and a human chondrosarcoma, but not in adult articular chondrocytes (Nakanishi et al, 1997).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The differential expression of the cytokine CTGF by adult articular chondrocytes, within 48 hr of transfer to suspension culture at 10 6 cells/ml ( Fig. 2A) was consistent with relatively low level of cell proliferation observed in suspension culture (Gagne et al, 2000). CTGF expression had been previously identified in chondrocytes derived from growth plate and a human chondrosarcoma, but not in adult articular chondrocytes (Nakanishi et al, 1997).…”
Section: Discussionsupporting
confidence: 82%
“…osition (Gagne et al, 2000). Northern blot analysis of mRNA from articular chondrocyte suspension cultures initially seeded at 10 4 , 10 5 , and 10 6 cell/ml revealed that the level of CTGF expressed was higher in suspension cultures seeded at lower cell density (Fig.…”
Section: Discussionmentioning
confidence: 92%
“…This result could be related to the post-mortem time when autopsy tissues were processed (within 2 4 4 8 h) whilst DAC was processed within 12 h after arthroscopic retrieval from patients during an ACI procedure. Articular cartilage from autopsies should be processed for cell culture within 24 h post-mortem [28] or within 48 h [9]. Although it has been shown that 88-96'%1 post-mortem human chondrocytes, kept at 4 "C within the first 4.5 days, are viable as observed by vital staining and confocal laser scanning 3D microscopy [16].…”
Section: Discussionmentioning
confidence: 99%
“…The heterogeneity of articular chondrocytes may also play a role in cell survival, proliferation and matrix synthesis [Panasyuk et al, 2004]. In addition, mitotic activity, seeded cell density and ECM composition may play important roles inasmuch as mutual infl uences are not fully understood yet [Paige et al, 1995;Gagne et al, 2000;Qi and Scully, 2003].…”
Section: Hydrogel Culturementioning
confidence: 99%